Nanomedicine‐Based Immunotherapy for the Treatment of Cancer Metastasis - Zhang, Pengcheng; Zhai, Yihui; Cai, Ying; Zhao, Yuliang; Li, Yaping (Advanced materials (Weinheim), 2019)
Metastasis is the leading cause of cancer‐associated death, with poor prognosis even after extensive treatment. The dormancy of metastatic cancer cells during dissemination or after colony formation is one major reason for treatment failure, as most drugs target cells of active proliferation. Immunotherapy has shown great potential in cancer therapy because the activity of effector cells is less affected by the metabolic status of cancer cells. In addition, metastatic cells out of immunosuppressive tumor microenvironment (TME) are more susceptible to immune clearance, although these cells can achieve immune surveillance evasion via strategies such as platelet and macrophage recruitment. Since nanomaterials themselves or their carried drugs have the capability to modulate the immune system, a great amount of focus has been placed on nanomedicine strategies that leverage immune cells participating the metastatic cascade. These nanomedicines successfully inhibit the tumor metastasis and prolong the survival of model animals. Immune cells that are involved in the metastasis cascade are first summarized and then recent and inspiring strategies and nanomaterials in this growing field are highlighted. Recent advances in nanomedicine‐based immunotherapy for the treatment of cancer metastasis are reviewed, starting with a brief introduction of metastasis cascade and nanomedicine‐based cancer immunotherapy. Recent strategies that can modulate key immune cells participating in metastasis cascade including cell intravasation and extravasation, blood circulation, and micrometastatic colony formation and proliferation are summarized.